AGARWOOD SUPPLY CHAIN MANAGEMENT IN CENTRAL JAVA PROVINCE - Nugroho Djati Satmoko (SEAN Institute, 2023)
This paper aims to analyze the supply of agarwood, the inhibiting factors of agarwood supply, and the amount produced from one agarwood tree in one harvest. Data was obtained from the head of a plantation farmer group in limpung sub-district, a Field Extension Officer in limpung sub-district, a branch office head in limpung sub-district, and company owners. The research method uses qualitative methods. The results of the study concluded that the supply of agarwood in November 2015 to August 2016 experienced a shortage and even a supply vacuum. Factors that hinder the availability of supplies are natural factors and vaccines or drugs injected into agarwood trees. The harvest obtained from one agarwood tree is 5 kg per tree assuming one harvest reaches 10 agarwood trees with a total amount of agarwood as much as 50 kg.